An Unusual Case of Median Neuropathy: Application of Short Segmental Sensory Nerve Stimulation. Issue 6 (November 2019) - Luetmer, Marianne T.; Laughlin, Ruple S.
Abstract : Summary: A 55-year-old woman presented with an 18-month history of intermittent left-hand paresthesias affecting her first, second, and third digits. A small, immobile, nontender midline mass on the volar aspect of the left wrist was also present. Evaluation included normal routine nerve conduction studies and needle electromyography. An ultrasound was performed in the electromyography laboratory, verifying median nerve involvement of the mass within the proximal carpal tunnel. This finding guided the electromyographer to perform the unconventional technique of sensory nerve short segmental stimulation across the carpal tunnel, which confirmed focal slowing across the lesion, achieving electrodiagnostic confirmation of median nerve impairment. This case of atypical carpal tunnel syndrome due to a median nerve schwannoma demonstrates both the utility and specificity of short segmental sensory stimulation in some cases of median neuropathy at the wrist and the value of sonography in the electromyography laboratory.